Participatory mapping as a tool for gill net fisheries management in the south-central coast of são paulo state - De Souza, Vitor Alberto; De Freitas, Débora Martins [UNESP] (Universidade Federal do Paraná, 2018)
The comprehension of how ishing efort is distributed spatially and through time is essential for the success of Marine Protected Areas (MPAs). In order to achieve this, participatory mapping has been used as a method to obtain spatial data from artisanal ishermen, promoting more participatory decision-making processes. In the region of Peruíbe, there are a range of management instruments that regulates the spatial distribution and establish ishing closure areas for this activity. In order to understand how the gill net artisanal isheries, afect the existing closure areas in this region, interviews with local ishermen were conducted, on which participatory mapping exercises were performed. Therefore, it was possible to estimate the spatial distribution of the gill net isheries in this region. There were points where densiication of ishermen was identiied and it was found that these points were located nearby the MPAs, therefore creating areas of incongruities between the conservation objectives established by the MPAs and the ishing activity. Thus, a better understanding of the reasons why the ishermen choose certain areas for ishing, as well as how they will behave in case of closure of existing ishing areas are necessary to achieve an efective management for the MAPs.
Mapeamento participativo como ferramenta para a gestão da pesca de emalhe no litoral centro-sul de São Paulo
Keywords: APA Marinha Litoral Centro; Isheries management; Participatory mapping